For homogeneous Kartvelian onomastic material (Kakheti : Kakhati) - Sherozia, Revaz (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
Kartvelian oral linguistic space can be conditionally divided into two types, Eastern and Western. These two forms of oral speech do not go beyond a single linguistic system. Therefore, it is completely natural for them to have common grammatical or lexical elements. Of particular interest is the onomastic material in which the history of the nation is reflected. The article discusses the names of the historical corners of Georgia Kakheti, Kukheti (Kakhi) and the relationship between the village of Kakhati on the Black Sea coast, in the Enguri River basin in western Georgia. It is assumed that these names are formed according to one common root (kakh). The Kakhetian and Kakhetian forms are distinguished only by the vowel part (e: a) of the top producer. Also, the name of the village on the right bank of the Enguri, the name of Tagilon-i (Atangeli) and the term Atengenoba in Khevsureti, are considered as stems made from one root (tangel). We think that the name of the village in western Georgia, Tagilon, meant the place dedicated to the feast dedicated to the Archangel, while Athena remained to celebrate this feast. In this case, the reason for the similarity of the East-West forms can be easily explained (in terms of toponymy, obviously, the meaning of a religious holiday would be overshadowed). Kakh-et: Like Kakh-at Tagilon: Atengena indicates the unity of Georgia and the Kartvelian linguistic space.